2021
DOI: 10.1088/1755-1315/755/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Whey Composite Edible Film with the Addition of Clove Essential Oil and Different Types of Plasticizer

Abstract: The purpose of this study was to determine the mechanical properties of the composite whey edible film with the addition of clove oil and different types of plasticizers. This research was conducted as a laboratory experiment and the variables observed were the mechanical properties of the composite whey edible film. This research was conducted using a Factorial Completely Randomized Design consisting of Factor A (clove oil concentration: 5%; 10% and 15%) and Factor B (a type of plasticizer): sorbitol and poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…The highest EAB values were observed for the P8A sample, which contained the lowest concentration of oil. The current findings are in line with a previous study, which found a small increase in tensile strength with an increase in the concentration of clove oil (Ervandi et al, 2021). Similarly, another study reported that an increase in oil concentration increases the softness of edible films, which ultimately decreases the EAB values (Maizura et al, 2007).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The highest EAB values were observed for the P8A sample, which contained the lowest concentration of oil. The current findings are in line with a previous study, which found a small increase in tensile strength with an increase in the concentration of clove oil (Ervandi et al, 2021). Similarly, another study reported that an increase in oil concentration increases the softness of edible films, which ultimately decreases the EAB values (Maizura et al, 2007).…”
Section: Resultssupporting
confidence: 94%
“…Generally, it has been observed that film samples with more TS show lower EAB values (Ervandi et al, 2021). This phenomenon is also observed in the current work.…”
Section: Mechanical Parameters (Tensile Strength and Elongation At Br...supporting
confidence: 89%
See 1 more Smart Citation
“…The lack of skilled workers is the third problem for e-commerce business actors. Business actors do not yet have skilled workers to control and develop their e-commerce [11]. Many MSMEs, especially micro businesses, still have difficulty accessing financing.…”
Section: The Role Of E-commerce Use Capital Availability and Business...mentioning
confidence: 99%
“…Therefore, films formed from lipid-composite whey generally have a good moisture barrier because lipid compounds are hydrophobic. To increase the flexibility, mechanical, and barrier properties of edible films, plasticisers (e.g., glycerol (Gly), sorbitol, sucrose, mannitol, and polyethylene glycol) are mixed into film-forming solutions (Abdollahzadeh et al, 2021;Fahrullah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%